SOCIAL MEDIA ENGAGEMENT IN FACEBOOK: THE CASE OF COLLEGE STUDENTS IN THAILAND - Thumsamisorn, Apiwan; Rittippant, Nattharika (NIDA Development Journal, 2013)
Abstract This empirical study aims to investigate the engagement in social media use of college students in Thailand. Since the growing popularity of social media in Thailand has drawn great attention from consumers, many businesses have adopted a Facebook page as a marketing tool to communicate with their customers and potential customers. The DeLone and McLean Information Systems success model is used as a theoretical model to investigate how different quality dimensions affect information system usage. Furthermore, online (i.e., social media) engagement is investigated in this study. Online engagement refers to the active relationship with a brand by a website or other computer mediated communications. Consequently, this study explores the key success factors in using social media such as a Facebook page in terms of quality issues regarding users’ satisfaction, behavioral intention, and social media engagement. In this study, data were collected from 277 college students using the questionnaire survey method. The results revealed that information quality and system quality were crucial factors in determining user satisfaction and behavioral intention, which directly affect social media engagement. บทคัดย่อ งานวิจัยในครั้งนี้ มีวัตถุประสงค์เพื่อศึกษาการใช้สื่อสังคมออนไลน์ของนักศึกษาในประเทศไทย เนื่องจากการใช้งานของสื่อสังคมออนไลน์ในสังคมไทยปัจจุบันได้รับความสนใจอย่างแพร่หลาย รวมไปจนถึงภาคธุรกิจต่าง ๆ ที่ได้ให้ความสนใจและเลือกใช้สื่อสังคมออนไลน์เป็นเครื่องมือทางการตลาดในการในการติดต่อสื่อสารกับลูกค้า การศึกษาในครั้งนี้ได้พัฒนามาจากตัวแบบความสำเร็จของระบบสารสนเทศของ DeLone และ McLean จากมิติคุณภาพในด้านต่าง ๆ ของสื่อสังคมออนไลน์ที่มีผลต่อการใช้งานของระบบ ทั้งนี้ การสร้างส่วนร่วมให้กับลูกค้าผ่านสื่อสังคมออนไลน์จึงถือเป็นปัจจัยสำคัญในการศึกษาวิจัย ความหมายโดยทั่วไปของสร้างส่วนร่วมออนไลน์ คือ ความสัมพันธ์เชิงรุกกับตราสินค้าผ่านทางเว็บไซต์หรือการติดต่อสื่อสารผ่านทางคอมพิวเตอร์ในรูปแบบต่าง ๆ ดังนั้น การศึกษาในครั้งนี้มุ่งเน้นการศึกษาหาความสัมพันธ์ทางด้านคุณภาพต่างๆของสื่อสังคมออนไลน์ เช่น ที่มีต่อความพึงพอใจในการใช้งานของระบบ พฤติกรรมความตั้งใจต่อการใช้งานของระบบ และ การสร้างส่วนร่วมของสื่อสังคมออนไลน์ที่มีผลต่อผู้ใช้งาน การวิจัยนี้เป็นการวิจัยเชิงสำรวจโดยใช้แบบสอบถามที่พัฒนามาจากการทบทวนวรรณกรรม โดยใช้กลุ่มตัวอย่างที่กำลังศึกษาอยู่ระดับชั้นปริญญาตรี จำนวน 277 คน ผลการวิจัยพบว่าคุณภาพของสารสนเทศ และคุณภาพของระบบเป็นปัจจัยสำคัญที่มีอิทธิพลต่อความพึงพอใจในการใช้งานของสื่อสังคมออนไลน์ และ พฤติกรรมความตั้งใจต่อการใช้งานของระบบ ซึ่งล้วนก่อเกิดการสร้างส่วนร่วมระหว่างลูกค้ากับภาคธุรกิจ การวิจัยครั้งนี้จะเป็นแนวทางในการปฏิบัติหรือนำไปประยุกต์ใช้ในการนำสื่อสังคมออนไลน์ให้ประสบความสำเร็จต่อธุรกิจ